LIFE, IMAGE AND AUTHORIAL CONCEPTION (On the Example of the Novel “A Walk Under the Thunderstorm”) - Maksud Asadov (International Journal of Literature and Language Studies, 2026)
This article examines the ideological and artistic features of the novel “A Walk Under the Thunderstorm” by the renowned writer Erkin Azam, with particular attention to its system of characters, their role in the development of events, and the author’s artistic conception.